Low-cost gravitational lensing: combining analogies from astronomical observations and the theory of gravitational lensing in the classroom - Montoya, Habib; Oliveira, Danyel (Cadernos de Astronomia, 2024)
The gravitational lensing effect offers a wide range of spectacular images of the sky that can awake the curiosity of students and the general population. In this work, we shall address an introduction to gravitational lensing with three main focus: understanding the phenomenon in astronomical images, illustrating the gravitational lensing effect with low-cost equipment, and show how a elementary mathematics can represents the galaxy-galaxy lensing. In particular, we illustrate some astronomical images, both with the low-cost equipment and with analytics solutions for the formation of images generated by gravitational lensing in galaxy scale. The solutions are easy to implement computationally, and can be accessible to advanced high school students and for undergraduate students in the STEM fields interested in the subject.
Keywords: general relativity; gravitational lensing; gravitational arcs; algebraic equation; astrophysics